Human Resource Business Partners: Recruitment, Coaching, and Leadership Development - Primadi Candra Susanto; Ni Nyoman Sawitri; Sugeng Suroso; Zahara Tussoleha Rony (International Journal of Integrative Sciences, 2023)
The purpose of this paper is to provide an overview of each variable that exists by providing answers from researchers in this paper, This research uses qualitative techniques in a way that is relevant to the literature. Literary studies are types or methods of academic writing in the form of literature research. Theoretical analysis and analysis of relationships between variables in Mendeley, Google Scholar, and other sourcebooks and online media journals,  research results The variables in this study are still rarely united in one study from various studies only coaching, and leadership development exist. Recommendations in the future are still very rare for researchers to mention between the variables that researchers try to express in this paper, so that in the future this research can be carried out with different methods and different objects to give color to the field of human resources, especially  those in the research of this  paper